FOREIGN POLICY ANALYSIS OF OPERATION PEACE SPRING BY TURKEY IN 2019 AS A FORM OF SECURITIZATION OF THE SYRIAN REFUGEE CRISIS - Prakasa, Maulana Wahyu; Wibowo, Prihandono (Universitas Nasional, 2021)
The outbreak of civil war in Syria since 2011 has resulted in 3.8 million Syrian refugees having to move to neighboring countries. Turkey is one of them, with the total number of refugees as of December 2020 reaching 3.6 million refugees who fled to Turkey. This led to the emergence of a refugee crisis in Turkey which caused various problems at home. One of the problems with the refugee crisis is that it causes high unemployment in Turkey and is one of the factors inhibiting the economy. As a form of securitization of the refugee crisis by the Turkish state, it has been responded to in various ways and one of them is the Operation Peace Spring’s foreign policy launched in 2019. This policy is in the form of military operations to occupy territories by Turkey in the northern part of Syria, with the aim of providing a